How to Find the Relevant Words Politicians Use in Twitter? - Oliveira, Lucas Santos de; Melo, Pedro O. S. Vaz de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
The dynamics of society are constantly changing by social media. Twitter has been standing out as one of the main platforms for information discovery and its political use have been growing since 2008. In this work we collected the public deputies tweets between 2013 and 2015 for topic extraction by means of computational models. However, due to the large number of irrelevant words from the data dictionary, we used tf-idf and Shannon’s entropy to identify and select relevant political words.